O menino-poeta: no olhar oblíquo, a poesia [Manoel de Barros] - DURAZZO, Leandro; GRÁCIA-RODRIGUES, Kelcilene (Texto Poético, 2013)
Resenha da obra: BARROS, M. de. Menino do mato. São Paulo: Leya, 2010.